Summary

These notes cover the topic of limits and continuity in calculus. The examples include one-sided and two-sided limits.

Full Transcript

MATH 101 Calculus I Notation: 𝒙 β†’ π’‚βˆ’ (π‘₯ approaches π‘Ž from the left) 𝒙 β†’ 𝒂+ (π‘₯ approaches π‘Ž from the right) Beware: βˆ’π’‚ β‰  π’‚βˆ’ +𝒂 β‰  𝒂+ Only appear in limits The One-sided Limits π’π’Šπ’Ž 𝒇 𝒙 π’Šπ’” 𝒄𝒂𝒍𝒍𝒆𝒅 𝒍𝒆𝒇𝒕 π’π’Šπ’Žπ’Šπ’• π’π’Šπ’Ž 𝒇 𝒙 π’Šπ’” 𝒄𝒂𝒍𝒍𝒆𝒅 π’“π’Šπ’ˆπ’‰π’• π’π’Šπ’Žπ’Šπ’• π’™β†’π’‚βˆ’...

MATH 101 Calculus I Notation: 𝒙 β†’ π’‚βˆ’ (π‘₯ approaches π‘Ž from the left) 𝒙 β†’ 𝒂+ (π‘₯ approaches π‘Ž from the right) Beware: βˆ’π’‚ β‰  π’‚βˆ’ +𝒂 β‰  𝒂+ Only appear in limits The One-sided Limits π’π’Šπ’Ž 𝒇 𝒙 π’Šπ’” 𝒄𝒂𝒍𝒍𝒆𝒅 𝒍𝒆𝒇𝒕 π’π’Šπ’Žπ’Šπ’• π’π’Šπ’Ž 𝒇 𝒙 π’Šπ’” 𝒄𝒂𝒍𝒍𝒆𝒅 π’“π’Šπ’ˆπ’‰π’• π’π’Šπ’Žπ’Šπ’• π’™β†’π’‚βˆ’ 𝒙→𝒂+ Two-sided Limit One-sided Limits 𝑰𝒇 π₯π’π¦βˆ’ 𝒇 𝒙 β‰  π₯𝐒𝐦+ 𝒇 𝒙 ⟹ π₯𝐒𝐦 𝒇 𝒙 = 𝒅𝒐𝒆𝒔𝒏′ 𝒕 π’†π’™π’Šπ’”π’• 𝑫𝑡𝑬 𝒙→𝒂 𝒙→𝒂 𝒙→𝒂 𝑓 π‘Ž = 𝑒𝑛𝑑𝑒𝑓𝑖𝑛𝑒𝑑 𝑓 π‘Ž =2 ☟ 𝑓 π‘Ž =1 limβˆ’ 𝑓 π‘₯ = 1 π‘Žπ‘›π‘‘ lim+ 𝑓 π‘₯ = 3 lim 𝑓 π‘₯ = 1 π‘Žπ‘›π‘‘ lim+ 𝑓 π‘₯ = 3 lim 𝑓 π‘₯ = 1 π‘Žπ‘›π‘‘ lim+ 𝑓 π‘₯ = 3 π‘₯β†’π‘Ž π‘₯β†’π‘Ž π‘₯β†’π‘Žβˆ’ π‘₯β†’π‘Ž π‘₯β†’π‘Žβˆ’ π‘₯β†’π‘Ž ⟹One-sided Limits are NOT equal ⟹One-sided Limits are NOT equal ⟹One-sided Limits are NOT equal ⟹ Two-sided Limit doesn’t exist ⟹ Two-sided Limit doesn’t exist ⟹ Two-sided Limit doesn’t exist lim 𝑓 π‘₯ = DNE lim 𝑓 π‘₯ = DNE lim 𝑓 π‘₯ = DNE π‘₯β†’π‘Ž π‘₯β†’π‘Ž π‘₯β†’π‘Ž ☟ 𝑓 π‘Ž =3 𝑓 π‘Ž =2 𝑓 π‘Ž = 𝑒𝑛𝑑𝑒𝑓𝑖𝑛𝑒𝑑 limβˆ’ 𝑓 π‘₯ = 2 = lim+ 𝑓 π‘₯ lim 𝑓 π‘₯ = 2 = lim+ 𝑓 π‘₯ limβˆ’ 𝑓 π‘₯ = 2 = lim+ 𝑓 π‘₯ π‘₯β†’π‘Ž π‘₯β†’π‘Ž π‘₯β†’π‘Žβˆ’ π‘₯β†’π‘Ž π‘₯β†’π‘Ž π‘₯β†’π‘Ž ⟹ One-sided Limits are equal ⟹ One-sided Limits are equal ⟹ One-sided Limits are equal ⟹ Two-sided Limit exist ⟹ Two-sided Limit exist ⟹ Two-sided Limit exist lim 𝑓 π‘₯ = 2 lim 𝑓 π‘₯ = 2 lim 𝑓 π‘₯ = 2 π‘₯β†’π‘Ž π‘₯β†’π‘Ž π‘₯β†’π‘Ž Method of working with Limit: 1. Graphical Method 2. Numerical Method 3. Algebraically Solution: Graph: Conjecture: sin π‘₯ sin π‘₯ limβˆ’ = 1 = lim+ π‘₯β†’0 π‘₯ π‘₯β†’0 π‘₯ sin π‘₯ ⟹ lim =1 π‘₯β†’0 π‘₯ Solution: The function 𝑓 π‘₯ = π‘₯βˆ’1 is undefined at π‘₯ = 1 π‘₯βˆ’1 π‘₯βˆ’1 π‘₯βˆ’1 limβˆ’ = 2 = lim+ π‘₯β†’1 π‘₯βˆ’1 π‘₯β†’1 π‘₯βˆ’1 π‘₯βˆ’1 ⟹ lim =2 π‘₯β†’1 π‘₯βˆ’1 𝒙 (classic) 𝐅𝐒𝐧𝐝 π’π’Šπ’Ž π’™β†’πŸŽ 𝒙 π‘₯ 1 𝑖𝑓 π‘₯ > 0 Solution: 𝑓 π‘₯ = = ቐ𝑒𝑛𝑑𝑒𝑓𝑖𝑛𝑒𝑑 𝑖𝑓 π‘₯ = 0 π‘₯ βˆ’1 𝑖𝑓 π‘₯ < 0 π‘₯ π‘₯ limβˆ’ = βˆ’1 π‘Žπ‘›π‘‘ lim+ =1 π‘₯β†’0 π‘₯ π‘₯β†’0 π‘₯ π‘₯ ⟹ lim = 𝐷𝑁𝐸 π‘₯β†’0 π‘₯ Infinite Limits: 𝟏 (classic) 𝐅𝐒𝐧𝐝 π’π’Šπ’Ž π’™β†’πŸŽ 𝒙 𝟏 Solution: 𝑓 π‘₯ = 𝒙 1 1 limβˆ’= βˆ’βˆž π‘Žπ‘›π‘‘ lim+ =∞ π‘₯β†’0 π‘₯ π‘₯β†’0 π‘₯ 1 ⟹ lim = 𝐷𝑁𝐸 π‘₯β†’0 π‘₯ Infinite Limits: Various cases: βˆ’βˆž decrease without bound π’π’Šπ’Žβˆ’ 𝒇 𝒙 = ࡜ increase without bound 𝒙→𝒂 ∞ 𝒙 β†’ 𝒂+ 𝒙→𝒂 increase without bound decrease without bound increase without bound from the right and left Infinite Limits: Various cases: βˆ’βˆž decrease without bound π’π’Šπ’Žβˆ’ 𝒇 𝒙 = ࡜ increase without bound 𝒙→𝒂 ∞ 𝒙 β†’ 𝒂+ 𝒙→𝒂 decrease without bound increase without bound decrease without bound from the right and left Vertical Asymptotes: of a function 𝑓 Example: Vertical ☟ Asymptote Vertical Vertical ☟ Vertical ☟ Asymptote ☟ Asymptote Asymptote Vertical Asymptotes: Example: 𝒙 = 𝟎 π’Šπ’” 𝒂 Vertical Asymptote of the graph of 𝒇 𝒙 = 𝟏 𝒙 Vertical Asymptote Example: 𝒙 = 𝟏 π’Šπ’” 𝒂 Vertical Asymptote of the graph of 𝒇 𝒙 = 𝟏 𝟐 Vertical Asymptote π’™βˆ’πŸ 1 1 π‘₯βˆ’1 2 Example: =πŸ‘ =𝟐 πŸπŸŽπŸπŸ• =βˆ’ 𝟏𝟏 =𝟎 𝝅 = 𝟐 Example: = π₯𝐒𝐦 𝒇 𝒙 βˆ’ π’π’Šπ’Ž π’ˆ 𝒙 + πŸ‘ π’π’Šπ’Ž 𝒉 𝒙 𝒙→𝒂 𝒙→𝒂 𝒙→𝒂 𝟐 = πŸ’ βˆ’ βˆ’πŸ‘ + πŸ‘ πŸ‘ =πŸ’+πŸ‘+𝟐 =πŸ— Example: π₯𝐒𝐦 𝒇 𝒙 π₯𝐒𝐦 𝒉 𝒙 𝒙→𝒂 𝒙→𝒂 = π’π’Šπ’Ž π’ˆ 𝒙 𝒙→𝒂 𝟐 πŸ’ = πŸ‘ βˆ’πŸ‘ πŸ– = πŸ‘ βˆ’πŸ‘ πŸ– = βˆ’πŸ— Example: = π₯𝐒𝐦 𝒇 𝒙 = πŸ’=𝟐 𝒙→𝒂 Example: = π₯𝐒𝐦 π’™πŸ βˆ’ πŸ’ π’π’Šπ’Ž 𝒙 + π’π’Šπ’Ž πŸ‘ π’™β†’πŸ“ π’™β†’πŸ“ π’™β†’πŸ“ = πŸ“πŸ βˆ’ πŸ’(πŸ“) + πŸ‘ = πŸπŸ“ βˆ’ 𝟐𝟎 + πŸ‘ =πŸ– Example: Solution: π₯𝐒𝐦 π’™πŸ• βˆ’ πŸπ’™πŸ“ + 𝟏 πŸ‘πŸ“ = πŸπŸ• βˆ’πŸ 𝟏 πŸ“ +𝟏 πŸ‘πŸ“ π’™β†’πŸ = πŸβˆ’πŸ πŸ‘πŸ“ =𝟎 Limit of Rational Functions: Polynomial Polynomial There are 3 cases to consider: Case 1: Case 1: Example: 𝟐𝟐 βˆ’ 𝟐 + 𝟏 πŸ’ βˆ’ 𝟐 + 𝟏 πŸ‘ = = = = βˆ’πŸ‘ πŸβˆ’πŸ‘ βˆ’πŸ βˆ’πŸ (βˆ’πŸ)πŸ‘ βˆ’πŸ” βˆ’πŸ βˆ’ πŸ” βˆ’πŸ• = 𝟐 = = =πŸ• (βˆ’πŸ) +𝟐(βˆ’πŸ) πŸβˆ’πŸ βˆ’πŸ πŸ“π’™πŸ‘ + πŸ’ πŸ“(𝟐)πŸ‘ +πŸ’ πŸ’πŸŽ + πŸ’ πŸ’πŸ’ 𝒄 π₯𝐒𝐦 = = = = βˆ’πŸ’πŸ’ π’™β†’πŸ 𝒙 βˆ’ πŸ‘ πŸβˆ’πŸ‘ βˆ’πŸ βˆ’πŸ Case 2: 𝑡𝒐𝒏𝒛𝒆𝒓𝒐 𝒁𝒆𝒓𝒐 Solution: ∞ or βˆ’βˆž or Doesn’t Exist Example: πŸβˆ’πŸ’ βˆ’πŸ = = = βˆ’βˆž (πŸ’ βˆ’ πŸ’)(πŸ’ + 𝟐) 𝟎+ πŸβˆ’πŸ’ βˆ’πŸ = = βˆ’ =∞ (πŸ’ βˆ’ πŸ’)(πŸ’ + 𝟐) 𝟎 = 𝑫𝑡𝑬 Case 3: 𝟎 𝟎 Solution: π‘­π’‚π’„π’•π’π’“π’Šπ’π’ˆ or rationalizing the numerator or denominator Example: πŸ— βˆ’ πŸπŸ– + πŸ— 𝟎 = (πŸ‘ βˆ’ πŸ‘) = 𝟎  π‘¨πŸ βˆ’ πŸπ‘¨π‘© + π‘©πŸ = 𝑨 βˆ’ 𝑩 𝟐 (𝒙 βˆ’ πŸ‘)(𝒙 βˆ’ πŸ‘) = π₯𝐒𝐦 = π₯𝐒𝐦 𝒙 βˆ’ πŸ‘ = πŸ‘ βˆ’ πŸ‘ = 𝟎 π’™β†’πŸ‘ (𝒙 βˆ’ πŸ‘) π’™β†’πŸ‘ Case 3: 𝟎 𝟎 Solution: π‘­π’‚π’„π’•π’π’“π’Šπ’π’ˆ or rationalizing the numerator or denominator Example: βˆ’πŸ– + πŸ– 𝟎 (πŸπŸ” βˆ’ πŸ’ βˆ’ 𝟏𝟐) 𝟎  = = (πŸπ’™ + πŸ–) = π₯𝐒𝐦 π’™β†’βˆ’πŸ’ (𝒙 + πŸ’)(𝒙 βˆ’ πŸ‘) 𝟐(𝒙 + πŸ’) 𝟐 𝟐 𝟐 = π₯𝐒𝐦 = π₯𝐒𝐦 = =βˆ’ π’™β†’βˆ’πŸ’ (𝒙 + πŸ’)(𝒙 βˆ’ πŸ‘) π’™β†’βˆ’πŸ’ (𝒙 βˆ’ πŸ‘) (βˆ’πŸ’ βˆ’ πŸ‘) πŸ• Case 3: 𝟎 𝟎 Solution: π‘­π’‚π’„π’•π’π’“π’Šπ’π’ˆ or rationalizing the numerator or denominator Example: πŸπŸ“ βˆ’ πŸπŸ“ βˆ’ 𝟏𝟎 𝟎 = = πŸπŸ“ βˆ’ πŸ“πŸŽ + πŸπŸ“ 𝟎  (𝒙 βˆ’ πŸ“)(𝒙 + 𝟐) (𝒙 + 𝟐) πŸ• = π₯𝐒𝐦 = π₯𝐒𝐦 = Case 2 π’™β†’πŸ“ (𝒙 βˆ’ πŸ“)(𝒙 βˆ’ πŸ“) π’™β†’πŸ“ (𝒙 βˆ’ πŸ“) 𝟎 π’™πŸ βˆ’ πŸ‘π’™ βˆ’ 𝟏𝟎 𝒙+𝟐 πŸ• π₯𝐒𝐦+ 𝟐 = π₯𝐒𝐦+ = + = +∞ π’™β†’πŸ“ 𝒙 βˆ’ πŸπŸŽπ’™ + πŸπŸ“ π’™β†’πŸ“ 𝒙 βˆ’ πŸ“ 𝟎 π’™πŸ βˆ’ πŸ‘π’™ βˆ’ 𝟏𝟎 π₯𝐒𝐦 = 𝑫𝑡𝑬 π’™πŸ βˆ’ πŸ‘π’™ βˆ’ 𝟏𝟎 𝒙+𝟐 πŸ• π’™β†’πŸ“ π’™πŸ βˆ’ πŸπŸŽπ’™ + πŸπŸ“ π₯π’π¦βˆ’ 𝟐 = π₯π’π¦βˆ’ = βˆ’ = βˆ’βˆž π’™β†’πŸ“ 𝒙 βˆ’ πŸπŸŽπ’™ + πŸπŸ“ π’™β†’πŸ“ 𝒙 βˆ’ πŸ“ 𝟎 Recall: Example: Solution: lim π’™βˆ’πŸ = πŸβˆ’πŸ = 𝟎  π’™β†’πŸ 𝒙 βˆ’ 𝟏 πŸβˆ’πŸ 𝟎 π’Žπ’–π’π’•π’Šπ’‘π’π’š 𝒖𝒑 & π’…π’π’˜π’ π’ƒπ’š 𝒕𝒉𝒆 π’„π’π’π’‹π’–π’ˆπ’‚π’•π’† 𝒐𝒇 π’™βˆ’πŸ π’™βˆ’πŸ 𝒙+𝟏 𝒙 βˆ’ 𝟏 which is 𝒙 + 𝟏 lim = lim π’™β†’πŸ 𝒙 βˆ’ 𝟏 π’™β†’πŸ π’™βˆ’πŸ 𝒙+𝟏 π’™βˆ’πŸ 𝒙+𝟏 = lim π’™β†’πŸ 𝒙 + 𝒙 βˆ’ 𝒙 βˆ’ 𝟏 π’™βˆ’πŸ 𝒙+𝟏 = lim π’™β†’πŸ π’™βˆ’πŸ = lim 𝒙+𝟏 = 𝟏+𝟏=𝟐 π’™β†’πŸ Limit of Piecewise-Defined Functions: 1 Example: π‘₯+2 π‘₯2 βˆ’ 5 π‘₯ + 13 𝟏 𝟏 𝟏 𝟐 π₯π’π¦βˆ’ 𝒇(𝒙) = π₯π’π¦βˆ’(π’™πŸ βˆ’ πŸ“ ) = πŸ— βˆ’ πŸ“ = πŸ’ π₯𝐒𝐦 𝒇 𝒙 = π₯π’π¦βˆ’ = = βˆ’ = βˆ’βˆž π₯𝐒𝐦 𝒇 𝒙 = π₯𝐒𝐦 (𝒙 βˆ’ πŸ“) π’™β†’πŸ‘ π’™β†’πŸ‘ π’™β†’βˆ’πŸβˆ’ π’™β†’βˆ’πŸ 𝒙+𝟐 βˆ’πŸ + 𝟐 𝟎 π’™β†’πŸŽ π’™β†’πŸŽ π₯𝐒𝐦+ 𝒇 𝒙 = π₯𝐒𝐦+(π’™πŸ βˆ’ πŸ“) = (βˆ’πŸ)𝟐 βˆ’πŸ“ = πŸ’ βˆ’ πŸ“ = βˆ’πŸ =πŸŽβˆ’πŸ“ π₯𝐒𝐦 𝒇(𝒙) = π₯𝐒𝐦+ 𝒙 + πŸπŸ‘ = πŸπŸ” = πŸ’ π’™β†’πŸ‘+ π’™β†’πŸ‘ π’™β†’βˆ’πŸ π’™β†’βˆ’πŸ = βˆ’πŸ“ π₯𝐒𝐦 𝒇(𝒙) = 𝑫𝑡𝑬 π₯𝐒𝐦 𝒇(𝒙) = πŸ’ π’™β†’βˆ’πŸ π’™β†’πŸ‘ 𝑛 𝑛 lim 𝑓 π‘₯ (e) π‘₯β†’βˆž = lim 𝑓 π‘₯ π‘₯β†’βˆž π‘₯β†’βˆž π‘₯β†’βˆž true The End Behavior of 𝒇 𝒙 as 𝒙 β†’ ±∞ Various cases: π’π’Šπ’Ž 𝒇 𝒙 = ∞ π’π’Šπ’Ž 𝒇 𝒙 = ∞ π’™β†’βˆ’βˆž π’™β†’βˆž π’π’Šπ’Ž 𝒇 𝒙 = βˆ’βˆž π’π’Šπ’Ž 𝒇 𝒙 = βˆ’βˆž π’™β†’βˆ’βˆž π’™β†’βˆž Basic limits as 𝒙 β†’ ±∞ βž€ π’π’Šπ’Ž π’Œ = π’Œ π’™β†’Β±βˆž 𝟏 β‘‘ π’π’Šπ’Ž =𝟎 Note: (infinite limits) π’™β†’Β±βˆž 𝒙 π’Œ  ∞=𝟎 𝟏 π’Œ βž‚ If 𝒂 > 𝟎, 𝒕𝒉𝒆𝒏 π’π’Šπ’Ž =𝟎 𝒂𝒏𝒅 = 𝟎, for π’Œ ∈ ℝ and 𝒂 ∈ β„€+ π’π’Šπ’Ž  π’Œ =∞ π’™β†’Β±βˆž 𝒙𝒂 π’™β†’Β±βˆž 𝒙 𝒂 𝟎 π’π’Šπ’Ž 𝒙 = ∞ βžƒ π’™β†’βˆž 𝒂𝒏𝒅 π’π’Šπ’Ž 𝒙 = βˆ’βˆž π’™β†’βˆ’βˆž  π’Œ+∞=∞ π’π’Šπ’Ž 𝒙𝒏 = ∞, 𝒏 = 𝟏, 𝟐, πŸ‘, πŸ’, β‹―  π’Œ βˆ’ ∞ = βˆ’βˆž βž„ π’™β†’βˆž βˆ’βˆž, 𝑛 = 1,3,5, β‹― (ODD) βž… π’π’Šπ’Ž 𝒙𝒏 = ࡜ π’™β†’βˆ’βˆž ∞, 𝑛 = 2, 4, 6, β‹― (EVEN) Basic limits as 𝒙 β†’ ±∞ Example: βž„ βž… βž„ βž… (a) π’π’Šπ’Ž π’™πŸ = ∞ (b) π’π’Šπ’Ž π’™πŸ = ∞ (c) π’π’Šπ’Ž π’™πŸ‘ = ∞ (d) π’π’Šπ’Ž π’™πŸ‘ = βˆ’βˆž π’™β†’βˆž π’™β†’βˆ’βˆž π’™β†’βˆž π’™β†’βˆ’βˆž βž… (e) π’π’Šπ’Ž πŸπ’™πŸ“ = 𝟐 π’π’Šπ’Ž π’™πŸ“ (f) π’π’Šπ’Ž πŸπ’™πŸ“ = 𝟐 π’π’Šπ’Ž π’™πŸ“ π’π’Šπ’Ž βˆ’πŸ•π’™πŸ” = βˆ’πŸ• β‹… ∞ (g) π’π’Šπ’Ž βˆ’πŸ•π’™πŸ” = βˆ’πŸ• π’π’Šπ’Ž π’™πŸ” (h) π’™β†’βˆ’βˆž π’™β†’βˆž π’™β†’βˆž π’™β†’βˆ’βˆž π’™β†’βˆ’βˆž π’™β†’βˆž π’™β†’βˆž βž„ βž„ = βˆ’βˆž =πŸβ‹…βˆž βž… = βˆ’πŸ• β‹… ∞ = 𝟐 β‹… βˆ’βˆž = βˆ’βˆž = βˆ’βˆž =∞ Basic limits as 𝒙 β†’ ±∞ Example: ☟ ☝ 𝝅 𝝅 π’π’Šπ’Ž π­πšπ§βˆ’πŸ 𝒙 =βˆ’ π’π’Šπ’Ž π­πšπ§βˆ’πŸ 𝒙 = π’™β†’βˆ’βˆž 𝟐 π’™β†’βˆž 𝟐 Limits of Polynomials as 𝒙 β†’ ±∞ Example: = π’π’Šπ’Ž βˆ’πŸ’π’™πŸ“ = βˆ’πŸ’ β‹… ∞ = βˆ’βˆž π’™β†’βˆž = π’π’Šπ’Ž βˆ’πŸ’π’™πŸ“ = βˆ’πŸ’(βˆ’βˆž) = ∞ π’™β†’βˆ’βˆž (c) π₯𝐒𝐦 (πŸ•π’™πŸ“ βˆ’ πŸ’π’™πŸ‘ + πŸπ’™ βˆ’ πŸ—) = π’π’Šπ’Ž πŸ•π’™πŸ“ = πŸ•(βˆ’βˆž) = βˆ’βˆž π’™β†’βˆ’βˆž π’™β†’βˆ’βˆž Limits of Rational Functions as 𝒙 β†’ ±∞ Method 1: Just find the highest degree in the denominator and divide every term by it. Example: πŸ‘π’™ πŸ“ πŸ“ πŸ“ + πŸ‘+ πŸ‘ + πŸ‘+𝟎 𝟏 = π’π’Šπ’Ž 𝒙 𝒙 = π’π’Šπ’Ž 𝒙 = ∞ = = π’™β†’βˆž πŸ”π’™ πŸ– π’™β†’βˆž πŸ– πŸ– πŸ” βˆ’ 𝟎 𝟐 βˆ’ πŸ”βˆ’ πŸ”βˆ’ 𝒙 𝒙 𝒙 ∞ Method 2: Just take the ratio of leading terms. Example: πŸ‘π’™ πŸ‘ 𝟏 = π’π’Šπ’Ž = π’π’Šπ’Ž = π’™β†’βˆž πŸ”π’™ π’™β†’βˆž πŸ” 𝟐 Limits of Rational Functions as 𝒙 β†’ ±∞ Example: πŸ“π’™πŸ‘ πŸ“π’™πŸ πŸ“ ∞ = π’π’Šπ’Ž = π’π’Šπ’Ž =βˆ’ = βˆ’βˆž π’™β†’βˆ’βˆž βˆ’πŸ‘π’™ π’™β†’βˆ’βˆž βˆ’πŸ‘ πŸ‘ πŸ’π’™πŸ 𝟐 𝟐 = π’π’Šπ’Ž = π’π’Šπ’Ž = =𝟎 π’™β†’βˆ’βˆž πŸπ’™πŸ‘ π’™β†’βˆ’βˆž 𝒙 βˆ’βˆž Limits Involving Radicals as 𝒙 β†’ ±∞ Example: π‘₯2 + 2 π‘₯2 + 2 = lim π‘₯ = lim π‘₯ π‘₯β†’βˆž 3π‘₯ βˆ’ 6 π‘₯β†’βˆž 3π‘₯ 6 βˆ’ π‘₯ π‘₯ π‘₯ π‘₯2 2 + π‘₯2 π‘₯2 = lim π‘₯β†’βˆž 3π‘₯ 6 βˆ’ π‘₯ π‘₯ 2 π‘₯ 2 = π‘₯ = π‘₯ (since π‘₯ β†’ ∞) + 1+ 2 π‘₯ = lim π‘₯β†’βˆž 6 3βˆ’ π‘₯ 2 1+ 𝟎 1 1 ∞ = = = 6 3 3 3βˆ’βˆžπŸŽ Limits Involving Radicals as 𝒙 β†’ ±∞ Example: π‘₯2 + 2 π‘₯2 + 2 = lim π‘₯ = lim π‘₯ π‘₯β†’βˆ’βˆž 3π‘₯ βˆ’ 6 π‘₯β†’βˆ’βˆž 3π‘₯ 6 βˆ’ π‘₯ π‘₯ π‘₯ π‘₯2 2 + π‘₯2 π‘₯2 = lim π‘₯β†’βˆ’βˆž 3π‘₯ 6 π‘₯ βˆ’π‘₯ 2 π‘₯ 2 = π‘₯ = βˆ’π‘₯ (since π‘₯ β†’ βˆ’βˆž) βˆ’ 1+ 2 π‘₯ = lim π‘₯β†’βˆ’βˆž 6 3βˆ’ π‘₯ 2 βˆ’ 1 + ∞ 𝟎 βˆ’ 1 βˆ’1 = = = 6 3 3 3βˆ’ 𝟎 ∞ Limits Involving Radicals as 𝒙 β†’ ±∞ Example: π‘₯ 3 βˆ’ 4π‘₯ + 5 + 10 π‘₯ 3 βˆ’ 4π‘₯ + 5 10 + 2 = lim π‘₯2 = lim π‘₯ 2 π‘₯ π‘₯β†’βˆž 2π‘₯ 2 βˆ’ 6 π‘₯β†’βˆž 2π‘₯ 2 6 βˆ’ 2 π‘₯2 π‘₯2 π‘₯ π‘₯ 3 4π‘₯ 5 10 βˆ’ + + π‘₯4 π‘₯4 π‘₯4 π‘₯2 = lim π‘₯β†’βˆž 2π‘₯ 2 6 βˆ’ 2 π‘₯2 π‘₯ 1 4 5 10 βˆ’ 3+ 4+ 2 π‘₯ π‘₯ π‘₯ π‘₯ = lim π‘₯β†’βˆž 6 2βˆ’ 2 π‘₯ 1 4 5 10 βˆžβˆ’βˆž+∞+ ∞ 0 = = =0 6 2 2βˆ’ ∞ Review of exponential and logarithmic functions (see page 52-60) Infinite Limits laws for exponential and logarithmic functions:  π’π’Šπ’Žπ’†π’™ = ∞ π’™β†’βˆž  π’π’Šπ’Ž 𝒆𝒙 = 𝟎 π’™β†’βˆ’βˆž  π’π’Šπ’Žπ’†βˆ’π’™ = 𝟎 π’™β†’βˆž  π’π’Šπ’Ž π’†βˆ’π’™ = ∞ π’™β†’βˆ’βˆž  π’π’Šπ’Žπ’π’π’™ = ∞ π’™β†’βˆž  π’π’Šπ’Ž+ 𝒍𝒏𝒙 = βˆ’βˆž π’™β†’πŸŽ Horizontal Asymptotes: A horizontal line π’š = 𝑳 is called a horizontal asymptote of the graph of a function 𝒇 if either π’π’Šπ’Ž 𝒇 𝒙 = 𝑳 or π’π’Šπ’Ž 𝒇 𝒙 = 𝑳 π’™β†’βˆž π’™β†’βˆ’βˆž Example: 𝟏 𝟏 π’π’Šπ’Ž = = 𝟎 π’™β†’βˆž 𝒙 ∞ ⟹ π’š = 𝟎 (X-axis) is horizontal asymptote π’π’Šπ’Ž(π‘₯ 2 + 1) = ∞ π’™β†’βˆž ⟹ There is NO horizontal asymptote πŸ‘π’™ + πŸ• πŸ‘π’™ πŸ‘ πŸ‘ π’π’Šπ’Ž = π’π’Šπ’Ž = π’π’Šπ’Ž = π’™β†’βˆž πŸ“π’™ βˆ’ 𝟐 π’™β†’βˆž πŸ“π’™ π’™β†’βˆž πŸ“ πŸ“ πŸ‘ ⟹ π’š = πŸ“ is horizontal asymptote Example: horizontal asymptote ☟ horizontal asymptote 𝝅 𝝅 π’π’Šπ’Ž π­πšπ§βˆ’πŸ 𝒙 =βˆ’ π’π’Šπ’Ž π­πšπ§βˆ’πŸ 𝒙 = π’™β†’βˆ’βˆž 𝟐 π’™β†’βˆž 𝟐 𝝅 ⟹ π’š = Β± 𝟐 are the horizontal asymptotes (π’π’Šπ’Ž+ 𝒇 𝒙 = π’π’Šπ’Žβˆ’ 𝒇 𝒙 ) 𝒙→𝒄 𝒙→𝒄 [That is, a function 𝒇 𝒙 is continuous at 𝒙 = 𝒄 if π’π’Šπ’Ž+ 𝒇 𝒙 = π’π’Šπ’Žβˆ’ 𝒇 𝒙 = 𝒇 𝒄 ] 𝒙→𝒄 𝒙→𝒄 Remark: Types of Discontinuities: removable discon. jump discon. (a) 𝒇 𝒄 π’Šπ’” 𝒏𝒐𝒕 π’…π’†π’‡π’Šπ’π’†π’… (b) π’π’Šπ’Ž 𝒇 𝒙 β‰  π’π’Šπ’Žβˆ’ 𝒇 𝒙 π’™β†’π’„βˆ’ 𝒙→𝒄 ⟹ π’π’Šπ’Ž 𝒇 𝒙 = 𝑫𝑡𝑬 𝒙→𝒄 infinite discon. removable discon. (c) π’π’Šπ’Ž 𝒇 𝒙 = ∞ (𝑫𝑡𝑬) (d) π’π’Šπ’Ž 𝒇 𝒙 β‰  𝒇 𝒄 𝒙→𝒄 𝒙→𝒄 Example: 𝟐𝟐 βˆ’ πŸ’ 𝟎 β‘  𝒇 𝟐 = = β‘  π’ˆ 𝟐 =πŸ‘ πŸβˆ’πŸ 𝟎 ⟹ 𝒇 𝟐 is undefined π’™πŸ βˆ’ πŸ’ πŸ’ βˆ’ πŸ’ 𝟎 πŸβˆ’πŸ πŸŽοƒ» β‘‘ π’π’Šπ’Ž = = ⟹ 𝒇 𝒙 is not continuous at 𝒙 = 𝟐 π’™β†’πŸ 𝒙 βˆ’ 𝟐 (𝒙 + 𝟐)(𝒙 βˆ’ 𝟐) ⟹ π’π’Šπ’Ž = π’π’Šπ’Ž 𝒙 + 𝟐 π’™β†’πŸ (𝒙 βˆ’ 𝟐) π’™β†’πŸ =𝟐+𝟐=πŸ’ βž‚ π’π’Šπ’Ž π’™β†’πŸ π’ˆ(𝒙) β‰  π’ˆ 𝟐 ⟹ π’ˆ 𝒙 is not continuous at 𝒙 = 𝟐 Example: β‘  𝒉 𝟐 =πŸ’ π’™πŸ βˆ’ πŸ’ πŸ’ βˆ’ πŸ’ 𝟎 πŸβˆ’πŸ πŸŽοƒ» β‘‘ π’π’Šπ’Ž = = π’™β†’πŸ 𝒙 βˆ’ 𝟐 (𝒙 + 𝟐)(𝒙 βˆ’ 𝟐) ⟹ π’π’Šπ’Ž = π’π’Šπ’Ž 𝒙 + 𝟐 = 𝟐 + 𝟐 = πŸ’ π’™β†’πŸ (𝒙 βˆ’ 𝟐) π’™β†’πŸ βž‚ π’π’Šπ’Ž π’™β†’πŸ 𝒉 𝒙 =𝒉 𝟐 =πŸ’ ⟹ 𝒉 𝒙 is continuous at 𝒙 = 𝟐 Example: πŸβˆ’π’™ π’™πŸ β‘  𝒇 𝟏 = 𝟏𝟐 = 𝟏 π’π’Šπ’Žβˆ’ 𝒇(𝒙) = π’π’Šπ’Žβˆ’ (𝟏 βˆ’ 𝒙) = 𝟏 βˆ’ 𝟏 = 𝟎 β‘‘ π’™β†’πŸ π’™β†’πŸ π’π’Šπ’Ž 𝒇(𝒙) = 𝑫𝑡𝑬 π’™β†’πŸ π’π’Šπ’Ž+ 𝒇(𝒙) = π’π’Šπ’Ž+ π’™πŸ = 𝟏 π’™β†’πŸ π’™β†’πŸ ⟹ 𝒇 𝒙 is not continuous at 𝒙 = 𝟏 Example: π’™πŸ + 𝟏 πŸ‘π’™ βˆ’ πŸ’ Solution: β‘  𝒇 𝟎 = πŸ‘ 𝟎 βˆ’ πŸ’ = βˆ’πŸ’ β‘‘ π’π’Šπ’Ž 𝒇 𝒙 = 𝑫𝑡𝑬 because π’™β†’πŸŽ π’π’Šπ’Ž 𝒇(𝒙) = π’π’Šπ’Ž+ (πŸ‘π’™ βˆ’ πŸ’) = βˆ’πŸ’ π’™β†’πŸŽ+ π’™β†’πŸŽ While, π’π’Šπ’Žβˆ’ 𝒇(𝒙) = π’π’Šπ’Žβˆ’ (π’™πŸ + 𝟏) = 𝟏 π’™β†’πŸŽ π’™β†’πŸŽ ⟹ 𝒇 𝒙 is not continuous at 𝒙 = 𝟎 Functions Continuous on an Interval: A function 𝒇 is continuous on 𝒂, 𝒃 or βˆ’βˆž, ∞ if 𝒇 is continuous at each 𝒙 = 𝒄 in the interval. 𝒂 𝑐 𝒃 𝑐 If 𝒇 is continuous on βˆ’βˆž, ∞ , we say that 𝒇 is continuous everywhere. Definition: At 𝒙 = 𝒄, 𝒇 is continuous from the left if π’π’Šπ’Žβˆ’ 𝒇(𝒙) = 𝒇(𝒄) 𝒙→𝒄 𝒇 is continuous from the right if π’π’Šπ’Ž+ 𝒇(𝒙) = 𝒇(𝒄) 𝒙→𝒄 Functions Continuous on an Interval: Example: Show that 𝒇 𝒙 = πŸ— βˆ’ π’™πŸ is continuous on its domain. Sketch the graph of 𝒇 𝒙. Solution: Find the domain: πŸ— βˆ’ π’™πŸ β‰₯ 𝟎 ⟹ πŸ— β‰₯ π’™πŸ ⟹ πŸ— β‰₯ π’™πŸ ⟹3β‰₯ π‘₯ ⟹ βˆ’πŸ‘ ≀ 𝒙 ≀ πŸ‘ ⟹ Domain = βˆ’πŸ‘,πŸ‘ We shall show that 𝒇 is continuous on βˆ’πŸ‘,πŸ‘. 𝒇 𝟎 =πŸ‘ β‘  At 𝒙 = 𝒄, βˆ’ πŸ‘ < 𝒄 < πŸ‘ π’π’Šπ’Ž 𝒇 𝒙 = π’π’Šπ’Ž πŸ— βˆ’ π’™πŸ = πŸ— βˆ’ π’„πŸ = 𝒇 𝒄 𝒙→𝒄 𝒙→𝒄 ⟹ 𝒇 continuous on βˆ’3,3 β‘‘ π’π’Šπ’Ž+ 𝒇(𝒙) = π’π’Šπ’Ž+ πŸ— βˆ’ π’™πŸ = πŸ— βˆ’ πŸ— = 𝟎 = 𝒇 βˆ’πŸ‘ π’™β†’βˆ’πŸ‘ π’™β†’βˆ’πŸ‘ βž‚ π’π’Šπ’Žβˆ’ 𝒇(𝒙) = π’π’Šπ’Žβˆ’ πŸ— βˆ’ π’™πŸ = πŸ— βˆ’ πŸ— = 𝟎 = 𝒇 πŸ‘ π’™β†’πŸ‘ π’™β†’πŸ‘ Thus, 𝒇 is continuous on its domain βˆ’πŸ‘,πŸ‘ Example: Solution: We solve π’™πŸ βˆ’ πŸ“π’™ + πŸ” = 𝟎 ⟹ π’™βˆ’πŸ π’™βˆ’πŸ‘ =𝟎 ⟹ 𝒙 = 𝟐 𝒐𝒓 𝒙 = πŸ‘ ∴ π’š is discontinuous at 𝒙 = 𝟐 𝒂𝒏𝒅 πŸ‘ Example: Solution: 𝒙 π’Šπ’‡ 𝒙 > 𝟎 𝒇 𝒙 = 𝒙 =ቐ 𝟎 π’Šπ’‡ 𝒙 = 𝟎 βˆ’π’™ π’Šπ’‡ 𝒙 < 𝟎 Since both 𝒙 and βˆ’π’™ are polynomails, we know 𝒇 is continuous everywhere, except possibly at 𝒙 = 𝟎. We check the continuity at 𝒙 = 𝟎: β‘  𝒇 𝟎 = 𝟎 =𝟎 π’π’Šπ’Žβˆ’ 𝒇(𝒙) = π’π’Šπ’Žβˆ’ (βˆ’π’™) = 𝟎 β‘‘π’™β†’πŸŽ π’™β†’πŸŽ So, 𝒇 𝒙 = 𝒙 is continuous at 𝒙 = 𝟎 π’π’Šπ’Ž 𝒇(𝒙) = π’π’Šπ’Ž+ (𝒙) = 𝟎 π’™β†’πŸŽ+ π’™β†’πŸŽ βž‚ π’π’Šπ’Ž 𝒇 𝒙 = 𝒇 𝟎 = 𝟎 π’™β†’πŸŽ Theorem: β€œThe composition of continuous functions is also continuous” If π’ˆ is continuous at 𝒙 and 𝒇 is continuous at π’ˆ(𝒙), then 𝒇 ∘ π’ˆ is continuous at 𝒙. π’ˆ 𝒇 π‘₯ π’ˆ(𝒙) 𝒇(π’ˆ 𝒙 ) π’‡βˆ˜π’ˆ Remark: The absolute value of a continuous function is also continuous. Example: If 𝒇 𝒙 = 𝒙 and π’ˆ 𝒙 = πŸ’ βˆ’ π’™πŸ , show that 𝒇 ∘ π’ˆ is continuous everywhere. Solution: π’‡βˆ˜π’ˆ 𝒙 =𝒇 π’ˆ 𝒙 = 𝒇 πŸ’ βˆ’ π’™πŸ = πŸ’ βˆ’ π’™πŸ Polynomial (continuous everywhere) Then 𝒇 ∘ π’ˆ is continuous everywhere by using the above remark. Example: Solution: π’™πŸ + π’Œπ’™ = πŸ‘ 𝒙 πŸ‘ When 𝒙 = 𝟏 ⟹ 𝟏 𝟐+π’Œ 𝟏 = 𝟏 ⟹𝟏+π’Œ=πŸ‘ βŸΉπ’Œ=πŸ‘βˆ’πŸ βŸΉπ’Œ=𝟐 Example: πŸβˆ’πŸ 𝟎 = 𝒄𝒐𝒔 = 𝒄𝒐𝒔  πŸβˆ’πŸ 𝟎 (𝒙 βˆ’ 𝟏)(𝒙 + 𝟏) = π’π’Šπ’Ž 𝒄𝒐𝒔 = π’π’Šπ’Ž 𝒄𝒐𝒔 𝒙 + 𝟏 = 𝒄𝒐𝒔 𝟐 π’™β†’πŸ (𝒙 βˆ’ 𝟏) π’™β†’πŸ 𝟎 = 𝟎 sin 𝟎 + cos 𝟎 = cos 𝟎 = 𝟏 𝟎 Theorem: β€œThe Squeezing Theorem” If π’ˆ 𝒙 ≀ 𝒇 𝒙 ≀ 𝒉 𝒙 for all 𝒙 β‰  𝒄, in some open interval contining 𝒄, and π’π’Šπ’Ž π’ˆ 𝒙 = 𝑳 = π’π’Šπ’Ž 𝒉 𝒙. 𝒙→𝒄 𝒙→𝒄 Then π’π’Šπ’Ž 𝒇 𝒙 = 𝑳 too. 𝒙→𝒄 Example: 𝟏 𝟐 β‹… sin 𝟐𝜽 sin 𝟐𝜽 = lim = 𝟐 lim =𝟐 𝟏 =𝟐 πœ½β†’πŸŽ πŸβ‹…πœ½ πœ½β†’πŸŽ 𝟐𝜽 π’”π’Šπ’ 𝒙 π’”π’Šπ’ 𝒙 𝟏 = π’π’Šπ’Ž = π’π’Šπ’Ž β‹… π’™β†’πŸŽ 𝒙 β‹… 𝒄𝒐𝒔 𝒙 π’™β†’πŸŽ 𝒙 𝒄𝒐𝒔 𝒙 𝟏 π’”π’Šπ’ 𝒙 𝟏 = π’π’Šπ’Ž π’π’Šπ’Ž π’™β†’πŸŽ 𝒙 π’™β†’πŸŽ 𝒄𝒐𝒔 𝒙 sec π‘₯ = 𝟏 π’π’Šπ’Ž 𝒔𝒆𝒄 𝒙 π’™β†’πŸŽ = 𝒔𝒆𝒄 𝟎 =𝟏 Example: 𝟏 sin πŸ‘π’™ sin πŸ‘π’™ β‹… = lim 𝒙 = lim 𝒙 π‘₯β†’πŸŽ 𝟏 π‘₯β†’πŸŽ sin πŸ“π’™ sin πŸ“π’™ β‹… 𝒙 𝒙 πŸ‘ sin πŸ‘π’™ = lim πŸ‘π’™ π‘₯β†’πŸŽ πŸ“ sin πŸ“π’™ πŸ“π’™ πŸ‘ sin πŸ‘π’™ lim πŸ‘π’™ = π‘₯β†’πŸŽ πŸ“ sin πŸ“π’™ lim π‘₯β†’πŸŽ πŸ“π’™ 𝟏 πŸ‘ lim sin πŸ‘π’™ = π‘₯β†’πŸŽ πŸ‘π’™ πŸ“ lim sin πŸ“π’™ π‘₯β†’πŸŽ πŸ“π’™ 𝟏 πŸ‘ = πŸ“ Example: Using squeezing thm. 𝟏 βˆ’πŸ ≀ 𝐬𝐒𝐧 ≀ 𝟏 for all 𝒙 β‰  𝟎 𝒙 𝟏 βˆ’πŸ β‹… 𝒙 ≀ 𝒙 β‹… 𝐬𝐒𝐧 β‰€πŸβ‹…π’™ 𝒙 1 𝟏 π’π’Šπ’Ž sin = 𝑫𝑡𝑬 βˆ’π’™ ≀ 𝒙 𝐬𝐒𝐧 ≀𝒙 π’™β†’πŸŽ π‘₯ 𝒙 𝟏 As 𝒙 β†’ 𝟎, π’”π’Šπ’ 𝟏 oscillates between βˆ’πŸ and 𝟏 π₯𝐒𝐦 βˆ’π’™ ≀ π₯𝐒𝐦 𝒙 π’”π’Šπ’ ≀ π₯𝐒𝐦 𝒙 𝒙 π’™β†’πŸŽ π’™β†’πŸŽ 𝒙 π’™β†’πŸŽ faster and faster. 𝟏 𝟎 ≀ π’π’Šπ’Ž 𝒙 π’”π’Šπ’ β‰€πŸŽ π’™β†’πŸŽ 𝒙 𝟏 ⟹ π’π’Šπ’Ž 𝒙 π’”π’Šπ’ =𝟎 π’™β†’πŸŽ 𝒙 𝑏>1 0

Use Quizgecko on...
Browser
Browser